2016
DOI: 10.1038/srep38117
|View full text |Cite
|
Sign up to set email alerts
|

Collisions in outer space produced an icosahedral phase in the Khatyrka meteorite never observed previously in the laboratory

Abstract: We report the first occurrence of an icosahedral quasicrystal with composition Al62.0(8)Cu31.2(8)Fe6.8(4), outside the measured equilibrium stability field at standard pressure of the previously reported Al-Cu-Fe quasicrystal (AlxCuyFez, with x between 61 and 64, y between 24 and 26, z between 12 and 13%). The new icosahedral mineral formed naturally and was discovered in the Khatyrka meteorite, a recently described CV3 carbonaceous chondrite that experienced shock metamorphism, local melting (with conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 24 publications
(37 reference statements)
2
15
0
1
Order By: Relevance
“…It is deposited at the Smithsonian Institution’s National Museum of Natural History, Washington DC, USA under the catalogue number USNM 7908. We also present evidence of a time sequence between the Al-Cu-Fe metal phases and silicate matrix, and document the petrological context of four new Al-Cu-Fe minerals, discovered in Grain 126A and recently reported in refs 14, 16 and 17. We note that the interpretation here of a reaction history is supported by preliminary studies on Grain 129, some results of which were reported in ref.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is deposited at the Smithsonian Institution’s National Museum of Natural History, Washington DC, USA under the catalogue number USNM 7908. We also present evidence of a time sequence between the Al-Cu-Fe metal phases and silicate matrix, and document the petrological context of four new Al-Cu-Fe minerals, discovered in Grain 126A and recently reported in refs 14, 16 and 17. We note that the interpretation here of a reaction history is supported by preliminary studies on Grain 129, some results of which were reported in ref.…”
Section: Introductionsupporting
confidence: 86%
“…Among the metal grains are four new Al-Cu-Fe minerals, which were recently reported in refs 14, 16 and 17. They include stolperite (AlCu) 16, 17 , kryachkoite ((Al,Cu) 6 (Fe,Cu)) 16, 17 , hollisterite (Al 3 Fe) 16, 17 , and an as-yet-unnamed quasicrystal 14 (denoted ‘ i -II’ ) .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1), as typically observed for other fragments of the Khatyrka meteorite 4,7,13,14 . Detailed examination by scanning electron microscopy, single-crystal X-ray diffraction, micro-computed tomography and transmission electron microscopy of fragments from Grain 126 associated to proxidecagonite revealed the presence of trevorite, diopside, forsterite, ahrensite, clinoenstatite, nepheline, coesite, stishovite, pentlandite, Cu-bearing troilite, icosahedrite, khatyrkite, taenite, Al-bearing taenite, steinhardtite, decagonite, hollisterite, stolperite and kryachkoite 4,5,7,13,1517 . The recovery of different Al-Ni-Fe crystalline (steinhardtite) and QC (decagonite) intermetallic phases, motivated a careful search for other metallic fragments, which led to the discovery of a particle with composition close to that of the known Al-Ni-Fe decagonal QC but with different diffraction characteristics.
Figure 1Micro-computed tomographic images (at different orientations) of the entire grain (labeled number 126).
…”
Section: Resultsmentioning
confidence: 99%
“…In the search through Khatyrka meteoritic fragments recovered from a 2011 expedition to the Koryak Mountains in far eastern Russia 36 , various other novel intermetallic phases have been uncovered 1316 , including a second Al-Cu-Fe icosahedral QC phase that differs from icosahedrite and that is the first QC to be discovered in nature before being synthesized in the laboratory 17 . However to date, no natural periodic approximants to quasicrystals have been reported.…”
Section: Introductionmentioning
confidence: 99%